Comparative Analysis of the Pattern of Severe Injury Due to Road Traffic Accidents in Children - Ye. A. Spiridonova; S. A. Rumyantsev; F. G. Sharshov; D. V. Prometnoy; A. V. Chernozubenko (Общая реаниматология)
Objective: to study stepwise differences in the severity and pattern of severe traumatic injuries due to road traffic accidents in patients during the qualified and specialized stages of medical care in the age groups of 1 month to 18 years in the Rostov Region. Material and methods. The 2004—2009 case reports were used to make a retrospective comparative assessment of the condition of victims with severe road traffic injury at care stages in 2 groups: 1) one-month- to 18-year-old children who had been primarily admitted to the qualified-stage intensive care units (n=61); 2) one-month-to 18-year-old patients from the intensive care unit of the Regional Children’s Hospital, referred from the qualified-stage intensive care units (n=133). Results. The number of specialized-stage children in grave and extremely extensive grave condition at the specialized stage was 14.7% more than that at the qualified stage (100 and 85.3%, espectively). Concomitant injury was encountered more frequently (by 13%) in the specialized-stage patients (73.7 and 60.7%, respectively). The severity of road traffic injury was determined mainly by brain injuries at the qualified irnd specialized stages (96.7 and 96.1%), by skeletal injuries (11.6% more frequently) and thoracic ones (9.8% more frequently) at the specialized stage. The prevalence of abdominal injuries at the qualified stage was 9.8% higher. The pattern of brain injury in the specialized-stage patients showed a preponderance of brain contusion and epidural hematomas by 18.5 and 6.5%, respectively. Conclusion. Severe thoracic and brain injuries (craniocerebral injuries, brain contusion, and intracranial hematomas) are an indication for patient referral to the specialized care stage in order to perform high-technological diagnostic and therapeutic methods. Key words: children, road traffic accidents, severe injury, medical care stages.